Introduction (The University of Nairobi Journal of Language and Linguistics, 2026)
The papers in this collection result from talks that were presented at the 16th NiloSaharan Colloquium, Nairobi, which was organized by a team of colleagues from the Institute of African Studies and Egyptology, Faculty of Arts and Humanities, University of Cologne and the Department of Linguistics and Languages, Faculty of Arts and Social Sciences, University of Nairobi from 29th to 31st August 2023.1 The conference was entitled “Linguistic, Sociocultural, and Indigenous Perspectives” and, as the title indicates, it offered a comprehensive and expansive view on the diversity of Nilo-Saharan studies, encompassing panels on phonetics, phonology, morphology, syntax, and semantics, as well as sociolinguistics and historical reconstruction. The panels, which promoted an indigenous perspective, treated issues such as the pragmatics of war and conflict and cattle color terms, as well as literature and heritage studies, where researchers from fields beyond language sciences and linguistics presented on topics as diverse as archeology, forgotten manuscripts, Bible translation, art, film, and architecture, encouraging lively discussions. The conference also included a special round table on “Heritage and/as language” with participants of the Nairobi-Aswan-Cologne Summer School, chaired by Heinz Felber and Anne Storch.
Keywords: Introduction; Nilo-Saharan; Linguistics